2011
DOI: 10.1002/zaac.201100290
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth of Al‐Rich Complex Metallic Phases in the System Al–Cr–Fe Using the Czochralski Method

Abstract: Complex metallic phases in the Al-Cr-Fe system are considered to be interesting because of their enhanced resistance against corrosion. Single crystal growth of the Al 4 (Cr,Fe) and Al 13 (Fe,Cr) 4 phases, which is a prerequisite for detailed studies is presented herein for the first time. Along with their binary end members Al 4 Cr and Al 13 Fe 4 growth of cm 3 -size crystals was achieved by using the Czochralski method from Al-rich solutions at temperatures of approximately 1000°C. Special emphasis is put on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Techniques for growing large intermetallic single-crystals involve growth by the Czochralski (e.g. in the Al-Cr-Fe system [ 141 ]) or Bridgeman (e.g. in the Yb TX system with T = Cu, Ag, Pt or Au and X = Sn or Sb) techniques as well as synthesis from metallic fluxes.…”
Section: Developments In Synthesismentioning
confidence: 99%
“…Techniques for growing large intermetallic single-crystals involve growth by the Czochralski (e.g. in the Al-Cr-Fe system [ 141 ]) or Bridgeman (e.g. in the Yb TX system with T = Cu, Ag, Pt or Au and X = Sn or Sb) techniques as well as synthesis from metallic fluxes.…”
Section: Developments In Synthesismentioning
confidence: 99%
“…Additionally, the compromised stability promotes the formation of other metastable phases, such as Al 6 Fe, in the Al-Fe alloy after the substitution of Cr and Mn. One should note that the formation of the metastable Al x Fe phase in Al-Fe alloys due to the addition of Cr and Mn has been reported [ 13 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, M elements easily substituted Fe-sites in the Al 13 Fe 4 phase. It has been reported that these four elements are more likely to occupy the Fe sites [39][40][41][42]. If M substitutes one Fe atom in the Al 13 Fe 4 unit cell, no phase transition occurs and the proportion of substituted atoms remains at~0.98 at%.…”
Section: Formation Enthalpy Of Al 13 Fe 4 Phasementioning
confidence: 99%
“…The polycrystalline cubic gamma phase was provided by the "Institut Jean Lamour (IJL)" of Nancy (France). Further details on the preparation of the different phases can be found in [8,[18][19][20]. Pure polycrystalline 99.99% at Al, 99.98% at Cr and 99.99% at Fe (Goodfellow, UK) were used as comparative reference materials.…”
Section: Methodsmentioning
confidence: 99%